Literacy and Numeracy Questions Based on Minimum Competency Assessments to Improve the Competency of Private High School Teachers - Hari Sugiharto Setyaedhi (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Teachers at one of the private high schools are not yet skilled in preparing AKM-based literacy and numeracy questions. This research aims to test the feasibility and effectiveness of developing AKM-based literacy and numeracy questions.  The feasibility test uses validation from evaluation experts, teaching materials and language, while the effectiveness test uses the t-test of the average pre-test and post-test scores. The research subjects were 80 private high school teachers in Surakarta. The experimental design in this research uses a Pre-Experimental design with a Pretest Posttest One Group Design design model. Data collection methods use observation, interviews, questionnaires and tests. This research uses an additive model. The data analysis technique was carried out descriptively qualitatively based on the validator's suggestions. Data analysis using SPSS.  The results of the feasibility test validation show that there is a significant difference between the average pretest and posttest scores for literacy and numeracy. The conclusion of this research is that the development of AKM-based questions has proven to be feasible and effective in improving the competence of private high school teachers in Surakarta. The implication of this research is increasing teacher competence in developing literacy and numeracy-based questions. The implications of this research are This assessment provides clear guidance on areas that require special attention, so that training and professional development can be focused on addressing deficiencies.